Influence of surface treatment on the in-vitro fracture resistance of zirconia-based all-ceramic anterior crowns - Schmitter, Marc; Seltitz, Gabriele; Bömicke, Wolfgang; Rues, Stefan (Dental materials, 2015)
Objectives: The purpose of this study was to assess the effect of surface treatment on the fracture resistance of zirconia-based all-ceramic anterior crowns. - Methods: Sixty-four zirconia-based all-ceramic anterior crowns, veneered by use of a press-on technique, were produced. For 48 crowns intraoral adjustment was simulated (A-group), 16 crowns remained unadjusted (WA-group). The adjusted area was then treated in three ways: 1. no further surface treatment; 2. polishing, with irrigation, using polishers interspersed with diamond grit for ceramics; and 3. polishing and glaze firing. Half of the specimens were loaded until fracture in an universal testing device without artificial ageing; the other crowns underwent thermocycling and chewing simulation before ultimate-load testing. Explorative statistical analysis was performed by use of non-parametric and parametric tests. In addition, fracture-strength tests according to ISO 6872 were performed for veneer ceramic subjected to the different surface treatments. Finite element analysis was also conducted for the crowns, and surface roughness was measured. - Results: Crowns in the A-group were more sensitive to aging than crowns in the WA-group (p=0.038). Although both polishing and glaze firing slightly improved the fracture resistance of the specimens, the fracture resistance in the WA-group (initial fracture resistance (IFR): 652.0 ± 107.7N, remaining fracture resistance after aging (RFR): 560.6 ± 233.3N) was higher than the fracture resistance in the A-group (polished: IFR: 477.9 ± 108.8N, RFR: 386.0 ± 218.5N; glaze firing: IFR: 535.5 ± 128.0N, RFR: 388.6 ± 202.2N). Surface roughness without adjustment was Ra=0.1 μm; for adjustment but without further treatment it was Ra=1.4 μm; for adjustment and polishing it was Ra=0.3 μm; and for adjustment, polishing, and glazing it was Ra=0.6 μm. Stress distributions obtained by finite element analysis in combination with fracture strength tests showed that fractures most probably originated from the occlusal surface. - SIGNIFICANCE: To improve fracture resistance and reduce the incidence of failure, extensive occlusal adjustment of veneered anterior zirconia restorations should be avoided. Neither polishing nor glazing could restore the fracture resistance to the level maintained with unadjusted crowns.
Gesehen am 07.07.2020